2010
DOI: 10.1002/cjg2.1515
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Onset of Uplifting for the Mid‐Upper Yangtze Area Since Indosinian Event

Abstract: The onset of uplifting of the Mid‐upper Yangtze area is constrained by the combination of analysis of apatite fission track (AFT) age and modeling of fission track length distribution. The results show that the general trend of onset of uplifting is characterized by decreasing westward in geological time for the different tectonic units in the Mid‐upper Yangtze area. Two episodes of uplifting in Jianghan basin occurred within 157~97 Ma and 10~0 Ma; Xiang'exi‐Wuling area experienced an uplifting in 137~0 Ma; E'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Further, this diverse exhumation of the MTB is consistent with the following aspects: (1) the onsets of uplifting for different tectonic units in the Mid-upper Yangtze area decrease westward (Yuan et al, 2010); (2) the Huangling Dome was formed in 165-100 Ma, in combination with the features of detrital AFT ages, thermal history and strata distribution etc. ; and (3) the Mesozoic intracontinental deformation in western Hunan and Hubei Provinces to eastern Sichuan Province was progressive with a large width and a long diachronous interval (Mei et al, 2010).…”
Section: Diverse Exhumationsupporting
confidence: 81%
“…Further, this diverse exhumation of the MTB is consistent with the following aspects: (1) the onsets of uplifting for different tectonic units in the Mid-upper Yangtze area decrease westward (Yuan et al, 2010); (2) the Huangling Dome was formed in 165-100 Ma, in combination with the features of detrital AFT ages, thermal history and strata distribution etc. ; and (3) the Mesozoic intracontinental deformation in western Hunan and Hubei Provinces to eastern Sichuan Province was progressive with a large width and a long diachronous interval (Mei et al, 2010).…”
Section: Diverse Exhumationsupporting
confidence: 81%
“…Our results show that the heat flow value in the Jianghan Basin ranges from 41.9 to 60.9 mW/m 2 . The statistical average for the nine measured heat flow values is 52.3±6.3 mW/m 2 , which is lower than the mean terrestrial heat flow of continental areas in China (Guo et al, 2005) and close to that of the Sichuan Basin (Yuan et al, 2010). The heat flow contour map of the basin (Fig.…”
mentioning
confidence: 62%
“…7). Yuan et al (2010) studied the onset of uplifting for the Jianghan Basin after the Indosinian event by combining the analysis of AFT ages with modeling of fission track length distribution, demonstrating that two episodes of uplifting occurred at157-97 Ma and 10-0 Ma.…”
mentioning
confidence: 99%
“…The results of the apatite fission track inversion suggested that the late uplift and erosion of the western Hubei and eastern Chongqing area started ca. 97 Ma (the Early Cretaceous, Yuan et al, 2010). Inferred from this result, the Early Cretaceous sediments should have existed in the past in this area.…”
Section: Deposition Characteristicsmentioning
confidence: 75%